RECOARCTATION AFTER SURGICAL CORRECTION OF COARCTATION OF THE AORTA IN CHILDREN AND ADOLESCENTS - Kuzmanović, Milica (Medicinski podmladak, 2025)
Introduction: Coarctation of the aorta (CoA) is a narrowing of the thoracic aorta, most often localized at the junction of ductus arteriosus. Data on risk factors for the development of recoarctation remain contradictory in literature.The aim: To determine the frequency of recoarctation and to identify risk factors for the recoarctation after surgical correction of CoA.Material and methods: The research included 94 patients who underwent surgery for coarctation of the aorta from 2012 to 2017. Demographic and clinical characteristics, preoperative, intraoperative, postoperative and echocardiographic parameters were observed. Pressure gradient over 25 mmHg immediately after operation is considered predictоr for recoarctation of the aorta. The data was processed using methods of descriptive and analytical statistics.Results: The median age at the time of surgery was 2 months (4 days-19 years). The dominant technique was extended end-to-end anastomosis (90.4%). Kaplan Meier survival analysis showed higher incidence of recoarctation in the group of patients with immediate postoperative gradient >25 mmHg (p 25 mmHg is an independent predictor for recoarctation after surgical correction of the coarctation of the aorta.
Keywords: coarctation of the aorta; recoarctation; risk factors; gradient